Waterlogging and salinity stress affecting growth and morphological character changes of Limnocharis flava - SIDIQ PERMANA PUTRA; SANTOSA SANTOSA; YUSTINA CAROLINA FEBRIANTI SALSINHA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Putra SP, Santosa, Salsinha YCF. 2023. Waterlogging and salinity stress affecting growth and morphological character changes of Limnocharis flava. Biodiversitas 24: 333-340. Salinity stress and waterlogging affect plant growth response. This study aims to determine the effect of variations in salinity concentration (NaCl) and water depth on the growth and morphological characters of Genjer (Limnocharis flava) plants. The study used a completely randomized design (CRD) with 5 replications with a variable depth of water (W) consisting of W0 = 0 cm from the soil surface, W1 = 5 cm from the soil surface, W2 = 10 cm from the soil surface, and treatment of variations in salt concentration. (NaCl) (S) as many as 4 levels, namely S0 = 0 ppm, S1 = 25 ppm, S2 = 50 ppm and S3 = 75 ppm. Statistical analysis with Analysis of Variance (ANOVA) showed the interaction of high NaCl concentration and higher water depth decreased wet weight, dry weight, height, length and width of leaves of L. flava. The concentration of NaCl significantly affects the growth morphology and anatomy of L. flava. The high concentration of NaCl reduced the wet weight, dry weight, height, length and width of the leaves of L. flava. The high concentration of NaCl causes changes in the anatomical structure of L. flava. Water depth significantly affects the growth morphology and anatomy of L. flava. The higher water depth reduces the wet weight, dry weight, height, length and width of the leaves of L. flava. There is an interaction between NaCl concentration and water depth. The high concentration of NaCl and high level of water depth reduced the wet weight, dry weight, height, length and width of the leaves of L. flava.